The Efficacy of Cinnamomum burmanii Extract on the Protection of Neuronal Cell Death in Haloperidol Induced Male Wistar Rats - Nita Parisa; MT Kamaluddin; Theodorus Theodorus (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Background Haloperidol is categorized as the first class antipsychotic drug. Long-term use of haloperidol may convey to increased Reactive Oxygen Species (ROS) that will yield oxidative damage which further leads to cell death. Several studies had identified the effects of cinnamon extract on cell death. This study aimed to determine the efficacy of cinnamon extract (Cinnamomum burmanii) on the protection of neuronal cell death in haloperidol-induced male Wistar white rats. Methods This study was experimental with pre and post-test design. Thirty male Wistar rats were divided into 5 groups, induced with haloperidol and followed by treatment. Caspase-3 and dopamine were assayed by ELISA sandwich method using ELISA kit. Mean difference of caspase expression and dopamine levels before and after induction were shown (p<0.05). Results There were mean differences of caspase-3 expression level in the positive control group, cinnamon extract of 100 and 200mg/kgBW before and after treatment (p<0.05). Whereas for dopamine levels, there were mean differences in positive control group, cinnamon extract of 50, 100 and 200mg/kgBW before and after treatment (p<0.05). With Post Hoc test, it was found that there were no mean differences of caspase-3 expression level between positive group with cinnamon extract group of 100 and 200mg/kgBW (p>0,05) and there were also no mean differences of positive group dopamine level with group of cinnamon extract of 100 and 200mg/kgBW (p>0.05). Conclussion Cinnamomum burmanii extract at dose of 100 and 200mg/kgBW were effective in the protection against neuronal cell death in haloperidol induced male Wistar white rats.